Application of Modern Management in the Conservation of Ecotourism in Mahuze Mandiri Wasur Local Village - Batlajery, Semuel; Longgy, Dodhy Hyronimus Ama (AIBPM Publisher, 2023)
The study aims to understand the application of modern management in the context of ecotourism in Mahuze Mandiri Wasur local village. The methodology used in this study is qualitative, involving five informants. Data collection techniques involve observation, interviews, and documentation. Data analysis is carried out in the form of data reduction, data presentation, and drawing conclusions. The research findings are as follows: (1). The application of quantitative management methods, especially mathematical models, computerized models, and statistical models, is recommended for Mahuze Ecotourism to enhance decision-making efficiency. Additionally, a scientific management approach should be implemented to ensure that all elements within the Mahuze independent Ecotourism organization can better adapt to global changes. (2). It is important to implement a systems management approach, where all elements within Mahuze independent Ecotourism have defined roles and collaborate to build an interconnected management system that facilitates the achievement of previously established organizational goals. (3). Leaders in independent Ecotourism are expected to apply contingency management to adapt to changes both internally and externally. Internally, leaders should monitor and adjust the elements within the organization to ensure they adapt to changes. Externally, it is crucial for all elements to conduct sustainability analysis to address changes that occur.